A(H3N2) antigenic variation of influenza is associated with low vaccine efficacy in the early 2018 influenza season in Mexico City - Victor Alberto Hernández-Hernández; Anjarath Lorena Higuera-Iglesias; Gabriel Palma-Cortes; Daniela Tapia-Trejo; Santiago Ávila-Ríos; Rubén Roberto González-Fernández; Luis Ángel Pérez-Moreno; Joaquín Alejandro Zuñiga-Ramos; Cristóbal Guadarrama-Pérez; José Luis Sandoval-Gutiérrez; Carlos Cabello-Gutiérrez, Dr (International Journal of Infectious Diseases, 2022)
Objectives: We evaluated the VE and the mutations of the viruses present in the Mexican population at the beginning of 2018. Methods: We diagnosed influenza in outpatients with a high-performance Rapid Influenza Diagnostic Test (RIDT) qRT–PCR. Descriptive statistics were used to describe the study population, while the chi-square test was used to determine clinical variables. VE was analyzed through a negative test design. We sequenced the hemagglutinin (HA) gene, performed a phylogenetic analysis, and analyzed the nonsynonymous substitutions both in and outside antigenic sites. Results: Of the 240 patients analyzed, 42.5% received the trivalent vaccine, and 37.5% were positive for influenza. The VE for the general population for any influenza virus type or subtype was 37.0%, while the VE for the predominant influenza A(H3N2) subtype was the lowest (19.7%). The phylogenetic analysis of HA showed the co-circulation of clades and subclades 3C.2a1, 3C.2a1b, 3C.2a2, 3C.2a2re, 3C.2a3, and 3C.3a with identities approximately 97-98% similar to the vaccine composition. Conclusion: Low VE was related to the co-circulation of multiple clades and subclades of influenza A(H3N2), with sufficient genetic and phenotypic distance to allow for the infection of vaccinated individuals.